Change-of-direction performance in elite soccer players: Preliminary analysis according to their playing positions - Sariati, Dorsaf; Hammami, Raouf; Chtara, Mokhtar; Zagatto, Alessandro [UNESP]; Boullosa, Daniel; Clark, Cain C. T.; Hackney, Anthony C.; Granacher, Urs; Souissi, Nizar; Zouhal, Hassane (MDPI, 2020)
Our objective was to examine the relationship between change of direction (CoD) performance, with (CoDb), and without the ball (CoDwb), and selected measures of physical fitness (jump performance, speed, balance) in elite soccer players, according to players’ positions. Forty elite male soccer players performed the change-of-direction and acceleration test (CODAT) with (CODATb), and without the ball (CODATwb), 5-and 20-m sprint tests, the 5-jump test (5JT), and the Y-balance test (YBT). Analyses of the whole sample showed significant correlations between all CODAT measures (CODATwb and CODATb, respectively) and sprint 5-m (r = 0.72, p < 0.001; r = 0.52, p < 0.01), sprint 20-m (r = 0.54, p < 0.03; r = 0.45, p < 0.05), jump (r = −0.62, p < 0.01; r = −0.64, p < 0.01) and balance (r = −0.50, p < 0.01; r = −0.83, p < 0.001) performances. Correlations were significantly different between player positions (defender, midfielder and striker). When examining the entire sample, the single best predictor of CODATwb was performance in the 5-m test with an explained variance of 52% (p < 0.001). For CODATb, the Y-balance performance explained 68% of the variance of performance (p < 0.001). In conclusion, soccer coaches and fitness trainers are advised to improve players’ CoD using neuromuscular training that mimic crucial match actions. Meanwhile, CoD testing and training should be designed in line with the demands of playing position.
Keywords: CoD; Dynamic performances; Football; Players’ position